2021
DOI: 10.1021/acs.jchemed.0c01329
|View full text |Cite
|
Sign up to set email alerts
|

The Important Role of Chemistry Department Chairs and Recommendations for Actions They Can Enact to Advance Black Student Success

Abstract: There is a severe shortage of Black scientists in the United States. Amid the recent national movement to dismantle systemic racism and racial injustices, many scientists publicly highlighted the prevalence of racist learning environments in STEM, contributing to the underrepresentation of Black students in STEM fields. Acknowledging this longstanding troubling reality, this article emphasizes the instrumental role of chemistry department chairs in advancing Black student success in chemistry and STEM broadly.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
(143 reference statements)
1
20
0
Order By: Relevance
“…A true commitment to equity research is centering those principles in every decision we make as researchers and practitioners.' ' (p. 71) We also agree with our colleagues in education research who call for disaggregating data in evaluative efforts (Mukherji et al, 2017;Bancroft, 2018;Bancroft et al, 2021;Collins and Olesik, 2021).…”
Section: Implications For Research and Practicesupporting
confidence: 81%
“…A true commitment to equity research is centering those principles in every decision we make as researchers and practitioners.' ' (p. 71) We also agree with our colleagues in education research who call for disaggregating data in evaluative efforts (Mukherji et al, 2017;Bancroft, 2018;Bancroft et al, 2021;Collins and Olesik, 2021).…”
Section: Implications For Research and Practicesupporting
confidence: 81%
“…Research has also found that URM students hold negative math and science motivational beliefs, which often leads to poor STEM performance compared to their majority counterparts [16]. Other research highlights the need to address institutional barriers to success, including racist learning environments [17], racial illiteracy amongst faculty in higher education, [18], and a lack of focus on the role faculty play in academic student success [19]. To address the systemic problems associated with URM student success in STEM, practitioners have studied the types of educational experiences that can contribute to positive outcomes.…”
Section: Stem Education and Urm Studentsmentioning
confidence: 99%
“…Minority ethnic individuals are significantly under-represented across chemistry education and employment, [1][2][3][4] providing an urgent issue for us to address as a chemistry community.…”
Section: Introductionmentioning
confidence: 99%